Assessment of the effect of transobturator tape surgery on women's sexual function using a validated questionnaire - Eunwook Joo; Mi Hyun Kang; Eun-Hee Yoo; Donguk Kim (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveWomen with pelvic floor disorders and urinary incontinence (UI) are at an increased risk of sexual dysfunction. The purpose of this study was to investigate the effect of surgery for UI on sexual function.MethodsWe retrospectively reviewed the charts of 82 women who underwent mid-urethral transobturator tape (TOT) surgery between March 2010 and December 2014. The Pelvic Floor Distress Inventory-20 (PFDI-20) and the Pelvic Organ Prolapse/Urinary Incontinence Sexual Function Questionnaire-12 (PISQ-12) were administered pre- and postoperatively.ResultsWe observed a significant increase in the total postoperative PISQ-12 scores compared to the preoperative scores (from 27.1±7.3 to 30.5±6.8, P<0.001). Improved sexual function was confirmed in the physical (13.3±4.5 vs. 15.8±3.5, P<0.001) and partner-related domains (6.7±2.6 vs. 7.4±2.4, P=0.001). Coital incontinence and preoperative urinary distress inventory score were significant factors influencing postoperative sexual function in women undergoing TOT surgery for UI after adjusting for age, body mass index, menopause, and preoperative PISQ-12 score in multivariate regression analysis.ConclusionTOT surgery for UI correction resulted in significant improvement in sexual function.